Efficacy of diaphragmatic breathing exercise on respiratory, cognitive, and motor function outcomes in patients with stroke: a systematic review and meta-analysis - Abdullahi, Auwal; Wong, Thomson WL; Ng, Shamay SM (Frontiers in Neurology, 2024)
Background Stroke disrupts the functions carried out by the brain such as the control of movement, sensation, and cognition. Disruption of movement control results in hemiparesis that affects the function of the diaphragm. Impaired function of the diaphragm can in turn affect many outcomes such as respiratory, cognitive, and motor function. The aim of this study is to carry out a systematic review and meta-analysis to determine the efficacy of diaphragmatic breathing exercise on respiratory, cognitive, and motor outcomes after stroke. Method The study was registered in PROSPERO (CRD42023422293). PubMED, Embase, Web of Science (WoS), PEDro, Scopus, and CENTRAL databases were searched until September 2023. Only randomized controlled trials comparing diaphragmatic breathing exercise with a control were included. Information on the study authors, time since stroke, mean age, height, weight, sex, and the protocols of the experimental and control interventions including intensity, mean scores on the outcomes such as respiratory, cognitive, and motor functions were extracted. Cochrane risks of bias assessment tool and PEDro scale were used to assess the risks of bias and methodological quality of the studies. Narrative synthesis and meta-analysis were used to summarize the results, which were then presented in tables, risk-of-bias graph, and forest plots. The meta-analysis was carried out on respiratory function [forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), FEV1/FVC, peak expiratory flow (PEF)] and motor function (trunk impairment, and internal and external oblique muscles activity). Results Six studies consisting of 151 participants were included. The results of the meta-analyses showed that diaphragmatic breathing exercise is only superior to the control at improving respiratory function, FVC (MD = 0.90, 95% CI = 0.76 to 1.04, P < 0.00001), FEV1 (MD = 0.32, 95% CI = 0.11 to 0.52, P = 0.002), and PEF (MD = 1.48, 95% CI = 1.15 to 1.81, P < 0.00001). Conclusion There is limited evidence suggesting that diaphragmatic breathing exercise may help enhance respiratory function, which may help enhance recovery of function post stroke. Systematic Review Registration PROSPERO, identifier CRD42023422293.